2022
DOI: 10.1093/rb/rbac016
|View full text |Cite
|
Sign up to set email alerts
|

Genetically engineered FGF1-sericin hydrogel material treats intrauterine adhesion and restores fertility in rat

Abstract: Endometrial injury can cause intrauterine adhesions (IUA) and induce the formation of endometrial fibrosis, leading to infertility and miscarriage. At present, there is no effective treatment method for severe IUA and uterine basal injury with adhesion area larger than 1/3 of the uterus. In this study, we prepared FGF1 silk sericin hydrogel material (FGF1-SS hydrogel) to treat endometrial injury and prevent endometrial fibrosis. Compared with the silk sericin hydrogel material (WT-SS hydrogel), FGF1-SS hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…The main cause of endometrial fibrosis is now considered to be abnormal migration and proliferation of uterine epithelial and mesenchymal cells, leading to abnormal secretion of extracellular matrix proteins and cytokines, resulting in the deposition of type I collagen in the endometrium to form endometrial fibrosis ( Hu et al, 2018 ; Cao et al, 2020 ). In the present study, FGF1 inhibited endometrial fibrosis, a result that was consistent with the earlier finding of Guan et al ( Guan et al, 2022 ) that hydrogel-bound FGF1 suppressed the process of intrauterine endofibrosis.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The main cause of endometrial fibrosis is now considered to be abnormal migration and proliferation of uterine epithelial and mesenchymal cells, leading to abnormal secretion of extracellular matrix proteins and cytokines, resulting in the deposition of type I collagen in the endometrium to form endometrial fibrosis ( Hu et al, 2018 ; Cao et al, 2020 ). In the present study, FGF1 inhibited endometrial fibrosis, a result that was consistent with the earlier finding of Guan et al ( Guan et al, 2022 ) that hydrogel-bound FGF1 suppressed the process of intrauterine endofibrosis.…”
Section: Discussionsupporting
confidence: 94%
“…While FGF1 has been studied in the past for its role in fat metabolism and diabetic wounds ( Wang et al, 2020a ; Deptula et al, 2021 ), its use in skin repair has also been reported in recent years ( He et al, 2019 ). In addition, Guan et al ( Guan et al, 2022 ) found that FGF1 combined with hydrogel could be used to treat intrauterine adhesions. On this basis, we hypothesized that FGF1 could promote endometrial thickening and facilitate recovery of endometrial function.…”
Section: Discussionmentioning
confidence: 99%
“…An important consequence of IUA is secondary fibrous tissue proliferation in the uterine cavity with partial or complete occlusion [48]. The prevalence of IUA in women ranges at 2–22% and affects female fertility [49].…”
Section: Discussionmentioning
confidence: 99%
“…Drug-loaded hydrogels and porous microfluidics allow for the combination of multiple therapeutics owing to their potent encapsulation capability, alleviating postoperative IUAs and improving endometrial repair [ 151 , 152 ]. Embedded active proteins and estrogen in bio-scaffolds endow them with antioxidant properties that protect against fibrosis within the uterine cavity and encourage the self-repair of the remaining endometrial cells by downregulating excessive oxidative stress and fibrosis-related mediators [ [153] , [154] , [155] , [156] , [157] ]. Administration of both SCs and their derivatives, such as human umbilical cord mesenchymal SCs (UCMSCs), mesenchymal SCs (MSCs), apoptotic bodies, and secretomes, in hydrogels and acellular scaffolds also potentially contribute to satisfactory endothelial regeneration after IUA [ [57] , [158] , [159] ].…”
Section: Application Of Bioengineering Technology In Endometrial Dise...mentioning
confidence: 99%